Mối quan hệ giữa cá thể và cộng đồng trong đạo đức học L.Kant (The relationship between individuals and community in Kantian Etihcs) - Vũ, Thị Thu Lan (Đại học Văn hóa Hà Nội, 2020)
One of the most important contributions with significant practical urgency for modern humankind is the thought of I. Kant on the relationship between individual and community, which the philosopher presented in his theory of morals. Rooting from his own criticism of empiricism, in which the thinker hypothesizes that all behaviors of an individual, if they are private interest or purpose personal gains, cannot be a behavior of indispensable nature, as they submit to the common rule of individual prosperity, Kant believed that individualism implicit in goals of empirical natural must be overcome by integrating the individuals into a species. Thus, I.Kant considered the goals and interests of humankind to be at a higher position than that of an individual. Accordingly, the transformation of an individual to a pro-community individual became the basic theme in Kantian ethics.